SSR loci potentially associated with high amylopectine content in maize kernel endosperm - S. I. Vakula; O. A. Orlovskaya; L. V. Khotyleva; A. V. Kilchevsky (Вавиловский журнал генетики и селекции)
As a component of functional nutrition, maize cultivars with “non-traditional” kernel composition (waxy, oilbearing, sugar, opaque, etc. phenotypic variants) are promising. Mutations in the waxy gene, which break down the structure and function of the enzyme for amylose biosynthesis, lead to a waxy (with a high content of amylopectin) endosperm formation. High variability of the waxy gene limits the use of microsatellite loci in marker associated selection of waxy maize genotypes. The increased frequency of gene rearrangements within the waxy locus facilitated the origination of many high-amylopectin corn lines carrying different SSR allelic variants. The purpose of this study was to evaluate the effectiveness of using waxy locus microsatellite sequences for identification and labeling of waxy maize genotypes. To this end, a complex of biochemical (calorimetry, bichromate method), molecular-genetic (SSR-PCR, capillary gel electrophoresis with fluorescent detection of fragments) and statistical (descriptive statistics, cluster analysis, χ2) analysis methods was used. Plant material used were 33 samples of corn kernels including mutant forms with a high content of amylose, amylopectin, short-chain starches, were kindly provided by VIR genetic collection (Russian Federation) and Maize Genetics Cooperation Stock Center (USA). The contents of starch, short-chain soluble carbohydrates, amylose, amylopectin in the grain of 33 maize samples were evaluated. Compositionally similar (to endosperm carbohydrates content) groups of samples were identified. They include 13 high-amylopectin samples carriers of waxy (wx) gene mutations and 20 samples with wild-type character (Wx). Molecular genetic screening of the collection included an analysis of the polymorphism of the microsatellite loci phi022, phi027, phi061 associated with the waxy gene sequence. Allelic composition of individual loci and their combinations were analyzed in relation to the accumulation of reserve carbohydrates in the kernel endosperm. Only the analysis of the phi022/phi027 combination or all three markers in the complex allows differentiating the wild Wx and mutant wx phenotypes of maize. It was shown that not the individual allelic polymorphisms of the phi022, phi027, phi061 loci are efficient for the markerassociated selection of high-amylopectin maize, but their unique combinations.